Analysis of Blasting Geometry on Blasting Production Results at PT Semen Bosowa Maros - Munir, Abdul Salam; Asmiani, Nur; Jafar, Nurliah; Wakila, Muhamad Hardin; Gouw, Jihan Fitri Ramdita Putri (International Journal of Applied Sciences and Smart Technologies, 2023)
Limestone mining for cement plants uses a blasting method to break the material. Blasting production is considered successful when it can achieve production targets based on tonnage of uncovered rock, efficient use of explosives, grain size or rock fragmentation, and environmental impact. This research aims to analyze the blasting geometry on the production results at the research location by knowing the initial design, the actual blasting geometry, and the geometry recommendation using the C.J. Konya method. In addition, researchers also know the explosives used, the production results in the form of material fractionation using the Kuz-Ram method and the tonnage of uncovered rocks. The initial design with a burden of 3.4 m, spacing of 3.4 m, hole depth of 5.9 m, and ANFO explosives per hole of 33 kg produced 147.31 tonnages. The actual geometry with a burden of 1.7 m, spacing of 3.5 m, hole depth of 6.0 m and ANFO explosives per hole of 26.73 kg produced a 77.11 tonnage. The actual geometry resulted in a blasting production of 6,941 tonnes per day, which did not meet the company's production target 10,639. The fragmentation calculation results obtained an average size in the field of 15.29 cm, which meets the required screening or sieve criteria of 0.80 - 1.00 m. The size of the fragments also follows the sieve calculation using the Kuz-Ram method, with a 100 cm sieve passing only 0.01%. Based on this, the company is recommended to make geometry changes to achieve the production tonnage target that has been set.